Metaphor and Metalanguage - Michiel Leezenberg (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
This paper consists of two sections: first, I return to the question of precisely which contextual factors are at work in metaphorical interpretation, and of the relation between asserted, presupposed and implied information; the upshot of this will be a renewed emphasis on metaphor as a discourse phenomenon. Second, I sketch a preliminary argument as to what a social practice account of metaphor might look like. Recent explorations of the contextual factors involved in the interpretation ofmetaphor make crucial use of David Kaplan’s Logic of Demonstratives, with its sophisticated treatment of context-dependence, and of the work on assertion developed by Stalnaker and others. All these approaches take contextual factors or parameters like that of speaker, time and place of utterance, etc., as given or primitive. Recent anthropological research, however, suggests that our practices constitute not only the contents of our utterances but also their contexts. Another recent development in linguistic anthropology is an increased attention to so-called language ideologies or metalinguistic beliefs, i.e., folk theories about the character and functioning of language. These insights suggest that metaphor is so thoroughly dependent on variable contextual and metalinguistic factors that it may well dissolve as a natural kind. At the very least, they suggest a shift away from the view of metaphor as a decontextualized sentence- or utterance-level phenomenon occurring in literate practices, which is still tacitly assumed in much literature on the topic.
Keywords: philosophy; linguistics